ជាប់ចំណង = Knotted : community focused social art practices as healing tools that binds us together : an exegesis presented in partial fulfilment of the requirements of the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Kham, Sopanha (Massey University, 2019)
ជឆប់ចំឆង (Knotted) explores Cambodia's architectural identity aligning it with a trajectory of Cambodia's history, political agendas, economic growth as well as global position. ជាប់ចំណង (Knotted) engages the cultural and architectural fabric of Cambodia, as a lens through which we might begin to gain a deeper understanding of our identity. The project explores the notion of identity, as a place where connections, conversations and discussions happen. I have applied a multiple approaches of making and facilitation including, poetry, collages, zine workshops, short documentaries, spatial installations as well as collections of conversations, photographs (archival and recent), videos (archival and recent). I work with these different materials and methodologies in order to gain a better understanding of the knotted nature ជាប់ចំណង (Knotted) of Cambodia's current cultural schema.